Study of serum homocysteine level in patients with chronic kidney disease and its association with renal function and serum albumin - Yadav, Vandana; Prakash, Vivek; Fiza, Bushra; Sinha, Maheep (International Journal of Research in Medical Sciences, 2020)
Background: Chronic kidney disease (CKD) includes irreversible destruction of nephrons leading to progressive decline in glomerular filtration rate. A preferential defect in Homocysteine disposal could hypothetically occur in CKD and subsequently lead to hyperhomocysteinemia. Understanding the status of Homocysteine and other parameters in CKD is useful in the management of the disease. Objective of the study is to estimate serum Homocysteine in CKD patients and its association with renal function and serum albumin in patients with CKD. Methods: The study design involves hospital based observational comparative study. The study was conducted in Department of Biochemistry in association with Department of Nephrology of Mahatma Gandhi Medical College and Hospital, Jaipur between May 2017 to June 2018. 100 diagnosed patients of CKD, visiting the Outpatient Department of Nephrology were enrolled as cases for the study. Patients having cardiovascular disease, Chronic liver disease, Age more than 60 years and pregnant females were excluded from study. The control group consists of 100 age and sex matched healthy individuals. Results: The mean serum creatinine levels of case and control group were 7.50±3.74 mg% and 0.83±0.22 mg% respectively. The mean of serum homocysteine levels of subject group was 27.35±12.52 µmol/L while the mean serum homocysteine levels of control group was 11.06±3.52 µmol/L. The serum homocysteine levels were significantly higher in the CKD patient group. The serum level of albumin in CKD patients and control group were 2.86±0.86 g/dl and 4.10±0.58 g/dl respectively. A positive correlation was found between serum creatinine and serum homocysteine levels. A negative correlation between serum homocysteine and serum albumin was found. Conclusions: Findings of the present study exhibit that serum homocysteine levels are elevated in CKD in comparison to healthy controls and it is positively correlated with serum creatinine level.